Mitigating Academic Burnout: Integrating Positive Psychology and Tawakkal Values in Islamic Education - Hirtsul Arifin; Halimatus Sakdia; Robiatul Adawiyah Hary Putri; Permata Billa Chatrina; Yuli Safitri (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The growing prevalence of academic burnout among students has emerged as a critical challenge within contemporary educational systems, including Islamic educational institutions that often prioritize cognitive achievement and religious discipline without sufficiently addressing psychological well-being. This study aims to examine the integration of Positive Psychology and Tawakkal as a holistic pedagogical framework for mitigating academic burnout in Islamic education. Employing a qualitative library research approach, the study systematically analyzed contemporary literature on Positive Psychology, student resilience, and academic burnout alongside classical and modern Islamic scholarship concerning Tawakkal and spiritual coping mechanisms. The findings reveal that the integration of psychological resilience strategies with the spiritual principle of Tawakkal produces an “active surrender” model capable of reducing toxic productivity, emotional exhaustion, and existential anxiety among students. Positive Psychology contributes adaptive coping, optimism, and emotional regulation, while Tawakkal provides metaphysical security and spiritual meaning that transform academic struggle into a process of purposeful ikhtiar. The study concludes that Islamic Education (PAI) possesses significant potential to evolve into a transformative well-being-oriented discipline integrating faith-based values with psychological science to support emotionally resilient and spiritually grounded learners in the twenty-first century.